‘Have you any recollection of what occurred at all?’: Davis v. Colchester County Hospital and Medical Negligence in Interwar Canada - Brown, R.; Hudak, Magen (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2015)
The history of medical malpractice in Canada has received little attention from legal or medical historians. Through a contextualized study of a Nova Scotia case from the 1930s, Davis v. Colchester County Hospital, this article demonstrates how changes in technology and surgical procedures both created situations that spurred malpractice claims, and made it difficult for injured patients to prove medical negligence. In addition, developments in tort law concerning the liability of hospitals, and the doctors and nurses working within them, provided medical defendants ample opportunity to avoid legal liability, even in cases in which the existence of negligent treatment was obvious. The testimony at trial, the legal strategies utilized by the lawyers, and the judicial rulings also shed light on attitudes of the medical profession toward personal responsibility and ethics, and demonstrates how the interests of patients were weighed against those of medical institutions and professionals by lawyers and judges.